Your blue is not my blue : a missing person memoir - Matis, Aspen (Little A, 2020)
When Aspen Matis's husband, Justin, left to attend a funeral, he never came back. Shock, grief, fear, and anger battled for control, but nothing prepared her for the disarming truth.